Assessment of Atrial Natriuretic Peptide (ANP) and Lipid Profile for Hypertension Patients in Thi-Qar province, Iraq - Haneen Kadhim Zaid; Khalid G. Al-Fartosi (University of Thi-Qar Journal of Science, 2021)
The present study was designed to assessment of atrial natriuretic peptide (ANP) and lipid profile of patients with hypertension in Thi-Qar province, Iraq. The sample included 70 patients, who were attending Al- Nasiryiah heart center during the period from February 2019 to June 2019, with 30 healthy as a control group. The results showed a significant increase.(P≤0.05) of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in hypertension patients compared with the control group. The level of atrial natriuretic peptide (ANP) showed a significant increase (P≤0.05) in patients compared with control group. Also the result indicated a significant increase (P≤0.05) of TC, TG, LDL and VLDL in patients compared with the control, while there was a significant decrease in HDL of patients compared with the control.